HUBUNGAN ANTARA STRES KERJA DAN SAFETY CLIMATE DENGAN KECELAKAAN KERJA PADA PENGEMUDI OJEK ONLINE DI TEMBALANG SEMARANG - Ribka Friday Hasian Napitu; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
As an online motorcycle taxi drivers who use a motorcycle are very vulnerable to have work accidents if they do not prioritize health and safety at work. Based on the theory of Loss Causation Model, work accidents can be caused by several things such as work stress and safety climate. Online motorcycle taxi drivers who experience work stress are caused by the demands of passengers and also the system implemented by the company. Those things can reduce concentration in work and cause work accidents. Also with the safety climate, online motorcycle taxi drivers who have bad perceptions about safety in working, will certainly work without prioritize to safety aspects, this can also lead to work accidents. The purpose of this study is to analyze the relationship between work stress and safety climate with work accidents on online motorcycle taxi drivers in Tembalang Semarang. This research is an analytic research using quantitative methods with cross sectional approach. The population sample in this study amounted to 70 people who were selected based on the accidental sampling method which was then analyzed by chi-square statistical analysis. Instrument that using in this study was questionnaire. Univariate analysis in this study were 74,3% respondents have work stress and 51,4% respondents have a good safety climate. The result of the bivariate analysis indicate that there is a relationship between work stress (p = 0.012) and safety climate (p = 0.047) with work accident on online motorcycle taxi drivers in Tembalang Semarang. Online motorcycle taxi drivers can can share their problems at work and the system implemented by the company with colleagues and also to the company. They must also attend safety riding training which will be required by the company to be followed by all online motorcycle taxi drivers.